A educação Karipuna do Amapá no contexto da educação escolar indígena diferenciada na aldeia do Espírito Santo - Brito, Edson Machado de (2012)
The thesis analyzes the history of school based between Karipuna Amapá, in the village of the Holy Spirit, located in the city of Oiapoque, analyzes focusing on discussions and actions to implement the indigenous school education in that village. At the core of the analysis of the stories appear Karipuna, its forms of social organization, their rituals and their traditional educational methods used in the formation of Karipuna. The study weaves a web of relationships they establish dialogue with local issues of national, following the movement of indigenous history, intertwined by the policies of the national state over time